2011
DOI: 10.3174/ajnr.a2878
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Thrombus Hounsfield Units on Noncontrast CT Predicts Stroke Subtype and Early Recanalization after Intravenous Recombinant Tissue Plasminogen Activator

Abstract: BACKGROUND AND PURPOSE:Little is known about the factors that determine recanalization after intravenous thrombolysis. We assessed the value of thrombus Hounsfield unit quantification as a predictive marker of stroke subtype and MCA recanalization after intravenous rtPA treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
112
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 124 publications
(119 citation statements)
references
References 36 publications
4
112
3
Order By: Relevance
“…There is emerging evidence that the success of recanalization efforts is largely driven by the structure of the occluding thrombus 4, 5, 6. Indeed, thrombus perviousness as evidenced by higher clot density is strongly associated with recanalization after intravenous recombinant tissue‐plasminogen activator (rt‐PA) treatment and favorable functional outcome 3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is emerging evidence that the success of recanalization efforts is largely driven by the structure of the occluding thrombus 4, 5, 6. Indeed, thrombus perviousness as evidenced by higher clot density is strongly associated with recanalization after intravenous recombinant tissue‐plasminogen activator (rt‐PA) treatment and favorable functional outcome 3.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the composition of the thrombus may provide additional information to determine the potential success of reperfusion efforts and individual prognosis. Several studies confirmed that a higher thrombus density is associated with improved reperfusion rates and better outcome, regardless of systemic or endovascular recanalization techniques 3, 4, 5, 6. Thrombus density can be determined noninvasively on noncontrast enhanced CT (NECT) and was shown to be dependent on source, time, and hematocrit, and is altered by treatment with antiplatelets 7, 8.…”
Section: Introductionmentioning
confidence: 97%
“…It has also been suggested that HMCAS due to cardio-embolism has higher vessel attenuation and is more likely to recanalise post-thrombolysis. 1 Previous angiographic studies show that HMCAS disappearance post-thrombolysis indicates recanalisation of occluded vessels. 10,11 Using HMCAS disappearance as a surrogate for MCA recanalisation, this study aimed to assess predictors of HMCAS disappearance in a realworld group of thrombolysed stroke patients.…”
Section: Introductionmentioning
confidence: 99%
“…1 In one large multicentre study (IST-3) 2 hyperdense arteries were seen in about a quarter of ischaemic strokes, predominantly in the anterior circulation. The presence of HMCAS was associated with worse outcomes but no increased risk of symptomatic haemorrhage following intravenous thrombolysis (IVT).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation